Flavonoids of Aptenia cordifolia - Elgindi, M.R.; Mabry, T.J.; Elgindi, O.D. (Asian Journal of Chemistry, 2010)
Two flavanone glycosides, liquiritin and naringenin and one flavanol glycoside, 3´4´-dihydroxy-7-methoxyflavonol 3-O-β-D-glucoside, were isolated and identified from the aerial parts of Aptenia cordifolia. In addition, the terpenoid sitosterol stigmasterol and the anthocyanidin pelargonidin were also detected. The structures of all compounds were established by chromatographic and spectroscopic methods. This is the first report of flavonoids from Aptellia cordifolia.